Intermediate Algebra: Connecting Concepts through Application

Published by Brooks Cole
ISBN 10: 0-53449-636-9
ISBN 13: 978-0-53449-636-4

Chapter 4 - Quadratic Functions - 4.4 Solving Quadratic Equations by the Square Root Property and Completing the Square - 4.4 Exercises - Page 346: 13


$x=6-\sqrt 3,6+\sqrt 3$

Work Step by Step

When taking the square root of a number, you get a positive and a negative answer. $-5(x-6)^2-15=-30$ $-5(x-6)^2=-15$ $(x-6)^2=3$ $x-6=\sqrt 3$ $x=6+\sqrt 3$ or $x-6=-\sqrt 3$ $x=6-\sqrt 3$. So $x=6-\sqrt 3,6+\sqrt 3$.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.